ANALISIS IS FINANCIAL STATEMENT BASAL FINANCIAL PERFORMANCE ESTIMATION ON PT. BANK NEGARA INDONESIA 1946 (Persero) Plc - Alfianto, Aditya; no, Sutris (Jurnal Ilmiah Mahasiswa FEB, 2013)
Bank health level can be assessed of severally indicator and one of main indicator that made by estimation basic is pertinent Bank financial statement. Base financial statement will get to account a number prevalent financial ratio made by estimation basic increases Bank health. Analisis result financial statement will help to interpretation various relationshipÂ  keys and trend who can give judgment basic about Bank success potency at approaching term. Bank management in do its effort is charged for everlastingly look after balance among liquidity preserve that adequately with fairly internal rate of return attainment and saturated capital requirement that is equal to correspond to its instilling type. That thing is needful because in its operation Bank besides do instilling in productive asset as: credit and worth letters, also give commitment and other services For that is done by analysis utilisedding to know bank finance developing via financial performance estimation. To measure corporate finance performance can utilize analisis's tool.Analysis the so called finance. Data analysis tech that is utilized in this research is: and time series method . Observational object in this research covers: (1) consolidation financial position Reportings Periods 2010 until 2012, (2) komprehensif's balance Reporting starts years 2010 until 2012. Data was taken from by publication bank on official website it. There is criterion even tobservational object that includes in this research category is BNI 1946 that have performed RUPS close binds books 2010-2012 and issue financial statements each year with year period basic calendar 31 Desember. Base study result analyses about financial performance estimation by use of finance Ratio on BNI 46 gotten by results: ratio count wholly get good been said / healthy because input even upon specified appreciative standard by Indonesia central Bank or even average banking industry. But then of yielding arithmetic ratio of year goes to year still available ratio which experience tren that despite negative still in good level. Â  Key Word: Financial Statement, Financial Performance, Financial Ratio. Â